Landslides in the hillside development in the Hulu Klang, Klang Valley - Abu Samah, Farisham (2006)
This paper has been written to study on rapid landslide occurrence at the hillside development areas, in the Hulu Kelang. Being an urban area and highly populated, the impacts of these tragedies are detrimental to humans and properties. From literature, it is found that less action were taken by the architects to learn from the mistakes. From the landslides investigations reports, it is shown that landslides were caused mainly by failures of the retaining wall and other combinations factor like lack of maintenance, less coordination during construction stage and design problem. The question is what are architect’s roles and contributions in reducing landslides in hillside development in Malaysia. The discussion will be on landslides: the causal factors, the impacts, mitigation actions and architectural aspects to be considered in designing the site plan. The site plan design that has been practiced on the hillside development area in the preview of the landslide tragedies that happened in Hulu Kelang. On the end the architect shall be aware of their roles and apprehend good design practice for hillside development in the future.